Lifestyle of people aged 60+ who report for preventive examination - Małgorzata Szamocka; Monika Anna Ameryk; Maciej Świątkowski (Journal of Education, Health and Sport, 2017)
Lifestyle, with such components as diet, food quality, nutritional status and physical activity in different age groups, including people aged 60+, is a popular research field. Between 1989 and 2014, the number of elderly people in Poland increased by nearly 3 million. Lifestyle, formed from the childhood, is a very important factor affecting a person’s heath status and quality of life, particularly in the elderly. The aim of the study was to assess the lifestyle of people aged 60+ who reported for a screening examination for the early detection of colorectal cancer.